Effect of purified soluble polysaccharides extracted from gray oyster mushroom [Pleurotus sajor-caju (Fr.) Sing.] on 3t3-L1 adipocytes - Decha Sermwittayawong; Kulwanit Patninan; Chanawee Jakkawanpitak; Somruthai Phothiphiphit; Siwarutt Boonyarattanakalin; Masashi Inafuku; Hirosuke Oku; Kusumarn Noipha; Nongporn Hutadilok-Towatana (Penerbit Universiti Kebangsaan Malaysia, 2020)
Functional mushroom polysaccharides have been known to the Asian traditional medicine for many years. The anti-obesity activity of mushroom polysaccharides has been illustrated both in vivo and in vitro. However, the effect of pure polysaccharides on isolated fat cells has not been demonstrated. In this study, we used hot water and ammonium oxalate to extract polysaccharides from gray oyster mushroom [Pleurotus sajor-caju (Fr.) Sing.] and subsequently purified with enzymatic digestion, solvent extraction and ion-exchange chromatography. One of the fractions, 7S1-1, has the highest yield and purity and contains polysaccharides with the molecular weight around 500 kDa. In addition, Fourier transformed infrared spectroscopy (FTIR) and monosaccharide composition analyses showed that this 7S1-1 sample contains mostly β-glucan and some mannan. We find that the 7S1-1 fraction does not affect the total amount of triglycerides in the 3T3-L1 adipocytes but promotes a release of glycerol of the fat cells, suggesting that the fraction does not inhibit adipogenesis but stimulates lipolysis. Laminarin, a small β-glucan, confers similar results to the 7S1-1 sample, but it could not stimulate lipolysis as well as the 7S1-1 sample. Therefore, these results suggest a potential anti-obesity activity of the mushroom polysaccharides.